The Study of Partial Discharge Test on Service-Aged Cable Termination - Trinai Laohapongpan; Theerayod Wiangtong; Sittipong Kerdmanee; Sakda Lacharochana; Siwakorn Jeenmuang; Norasage Pattanadech (My University, 2023)
This paper presents the partial discharge (PD) testing on the plug-in gas-insulated switchgear cable termination taken out of service. The shield electrodes were designed to geometrically electric field control in the area of the insulation screen edge of the cable part. The PD test of the cable termination was performed. In addition, a computed radiography technique with X-ray was also performed to evaluate the mechanical integrity of the supporting spring of the cable termination. The fatigue of the supporting spring was evidenced. Moreover, the cable termination was disassembled and re-assembled to perform the PD test again. The PD characteristics, including PD magnitude, PD inception voltage (PDIV), and phase-resolved PD (PRPD) patterns, were reported. The PD test results revealed that the PDIV was lower than the operating voltage. Besides, the PRPD patterns exhibited internal discharge inside the cable termination. From the PD test results and computed radiographic, it was assumed that they might be caused by discharge in the interface between the stress cone and epoxy insulator.
Keywords: Advanced Computing and Algorithms; High voltage insulation and dielectric phenomena; Advanced Fiber Optic Sensors